What do intra-household experiments measure? Evidence from the lab and field - Hoel, Jessica B.; Hidrobo, Melissa; Bernard, Tanguy; Ashour, Maha (Elsevier, 2021)
Household economists have recently begun to use laboratory experiments to study behavior between spouses. While several connect inefficiency in the lab to specific constraints on decision-making (e.g. information asymmetries), few connect behavior in the lab to behavior and decision-making structures in the field. We study both efficiency and the decision-making process in semi-nomadic pastoralist households in Senegal with detailed survey data, vignettes, and public goods games. We find that inefficiency in a public goods game is correlated with larger gender gaps in milk production, an indicator of productive inefficiency at home. However, households that behave more efficiently in the lab report less collaborative decision-making at home. Our results suggest that lab games between spouses are measuring behavior meaningful to field outcomes, but that collaborative decision-making is not necessary to achieve efficiency.